Factors Influencing Environmental Sustainability Disclosure in the Palm Oil Plantation Sector - Masruddin, Masruddin; Muliati, Muliati; Mile, Yuldi; Pakawaru, Muhammad Ilham; Paranoan, Selmita (Institut Bisnis dan Informatika Kesatuan, 2025)
The disclosure of Environmental and Social Responsibility has become increasingly important in the palm oil plantation industry, especially in Indonesia, where environmental and governance issues are often under public scrutiny. This study aims to examine the factors that influence Corporate Social Responsibility (CSR) disclosure in the financial statements of palm oil companies listed on the Indonesia Stock Exchange (IDX). The variables analyzed include profitability, liquidity, leverage, company age, the presence of an independent board of commissioners, and foreign ownership. Using a purposive sampling method, the research selected 10 palm oil plantation companies that reported CSR information from 2016 to 2021, resulting in 60 financial statement observations. Multiple regression analysis was applied to determine the influence of the selected variables on CSR disclosure. The findings indicate that all examined variables significantly affect the level of CSR disclosure. The study concludes that firms with higher profitability, better liquidity, lower leverage, longer operational history, independent oversight, and foreign ownership are more likely to provide comprehensive CSR disclosures in their financial reports.